CRETACEOUS THERMAL EVENT AROUND THE GONGSUWON THRUST IN THE NORTHEASTERN OKCHEON BELT: EVIDENCE FROM RB−SR GEOCHRONOLOGY OF PALEOZOIC SEDIMENTARY ROCKS - Sagong H.; Kwon S.; Han R.; Ree J. (My University, 2006)
The Gongsuwon thrust together with the Deokpori (Gakdong) thrust in northeastern Okcheon belt is considered to be an important structure in understanding the tectonic evolution of the Korean peninsula following the Permian-Triassic collision between North and South China continents. We obtained Rb-Sr ages for Paleozoic sedimentary rocks around the Gongsuwon thrust to determine the age of petrographically observed thermal metamorphism and possibly constrain the movement age of the thrust. Andalusite, codierite and biotite porphyroblasts overgrow cataclastic foliation of siliceous fault rocks in the Gongsuwon thrust, indicating a post-faulting thermal metamorphism. A marble of the early Paleozoic Makgol Formation in the hanging wall (~200 m northwest from the fault zone center) and a siliceous cataclasite in the fault zone center gave Cretaceous Rb-Sr whole rock fragment ages: 113±21 (2σ) Ma and 68±17 (2σ) Ma, respectively. Sandstones of the late Paleozoic Hambaeksan Formation in the footwall (about 680 m southeast from the fault zone center) yielded an early Tertiary Rb-Sr biotite age of 56.3±6.0 (2σ) Ma, but a Paleoproterozoic Rb-Sr muscovite age of 1774±30 (2σ) Ma, suggesting that the early Tertiary thermal effect for the sandstones was strong enough to reset the Rb-Sr biotite age but weak enough not to affect the Rb-Sr muscovite age, i.e., between ~300°C and ~500°C, and that detrital muscovites in the sandstones were derived from the Precambrian basement rocks. These isotopic ages suggest that there was Cretaceous to early Tertiary thermal event around the Gongsuwon thrust, which is probably associated with well-known plutonism at that time (so-called Bulguksa granite). Available age data, albeit limited, suggest that Cretaceous to early Tertiary thermal metamorphism in the Taebaeksan basin might have been extensive. The movement age of the Gongsuwon thrust is constrained to be older than ~60 Ma.
Keywords: GONGSUWON THRUST; CRETACEOUS THERMAL EVENT; RB−SR GEOCHRONOLOGY; Cretaceous; Triassic; Permian; Cambrian; Paleoproterozoic; Mesozoic::Cretaceous; Мезозой::Меловая; Mesozoic::Triassic; Мезозой::Триасовая; Paleozoic::Permian; Палеозой::Пермская; Paleozoic::Cambrian; Палеозой::Кембрийская; Precambrian::Proterozoic::Paleoproterozoic; Докембрий::Протерозой::Палеопротерозойская